Changes in Violence and Clinical Distress Among Men in Individual Psychotherapy for Violence Against Their Female Partner: An Explorative Study - Askeland, Ingunn Rangul; Birkeland, Marianne Skogbrott; Lømo, Bente; Tjersland, Odd Arne (Frontiers in Psychology, 2021)
Most interventions for men who have acted violently towards their partner have been conducted as group interventions within a criminal justice context. Therefore, few studies have examined individual psychotherapy and how such interventions may reduce partner violence. In this study, we aimed to describe changes in violence, and changes in clinical distress in men undergoing individual psychotherapy targeting their use of partner violence, at a clinic organized within a psychosocial health care context. This is a naturalistic prospective study of men voluntarily receiving individual psychotherapy for their use of violence against their female partner. Participants were 84 male clients, and data on their use of physical violence, physical controlling violence, property violence and psychological violence were collected pretreatment, posttreatment and at follow-up 1.5 years after treatment from both the men, and their partners (n = 58). The percentage of use of all types of violence during a typical month the last year decreased from pretreatment to follow-up, according to both the men, and their partners. Over the course of treatment, use of all types of self-reported violence during the last month was reduced, however, this was only partially confirmed by their partners. Number of sessions was associated with a lower risk of having used physical and physically controlling violence 1.5 years after treatment. Alcohol abuse or dependency, or qualifying for one or more psychiatric diagnoses, were not associated with levels or change in use of violence. On average, the men’s clinical distress declined over the course of psychotherapy. The findings suggest that individual psychotherapy may be a promising and worthwhile intervention for intimate partner violence. Studies with more elaborate designs are needed to identify the core mechanisms of psychotherapy for violence, and to corroborate these results with higher levels of evidence.